Adolescence study deviant behavior - Шамардина, Марина (Pedagogy and Psychology, 2021)
The article systematically presents a theoretical analysis of approaches to such psychological phenomena as "resilience" and "emotional intelligence", shows their structural components. Attempts have been made, taking into account theoretical approaches, to show the presence of the relationship between emotional intelligence and resilience. A refined characteristic of the age period is given - adolescence: neoplasms, features of interpersonal interactions, a leading type of activity, the formation of emotional intelligence and its manifestation in stressful situations, taking into account the formation of possible deviation at a given age. An empirical study is presented that shows the features of emotional intelligence in the context of the formation of the components of resilience in deviant adolescents. The characteristics of emotional intelligence and resilience in deviant adolescents are described. The characteristics of emotional intelligence and resilience in deviant adolescents are described, which are manifested in the ability to be aware of their emotions and manage them, self-control, which are the basis for the formation of attitudes of resilience, and a low level of vitality and intrapersonal emotional intelligence can act as factors influencing the occurrence of deviant beha